Implementasi Pemasaran Digital Melalui Copywriting Produk Pada CV Lozy Hijab - Astuti R, Wanda Puspa Dewi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
In the digital era, marketing is the main key in maintaining and developing business, especially in industry fashion women as faced by Lozy Hijab. One of the marketing techniques that is the main focus of Lozy Hijab is copywriting in platform Whatsapp Business who face challenges. Therefore, this research aims to find a solution to this problem through object observations carried out with the aim of finding a formula for follow-up effective products, increase consumer interest, strengthen customer loyalty, and increase product closing in platform Whatsapp Business. The research method used is observation by analyzing customer responsiveness to copywriting products. The observation results show that copywriting that is well structured, includes important information clearly, and is supported by attractive product visualization can increase customer response and the chance of closing the product. Besides that, copywriting also has an indirect impact on the overall marketing of Lozy Hijab products, through platform e-commerce. This research contributes to the understanding and development of digital marketing strategies, especially in a business context fashion online, as well as emphasizing it is importance copywriting in achieving success in product marketing.